Nonuniqueness of Solutions to the Lp Dual Minkowski Problem. (9th March 2021) - Li, Qi-Rui; Liu, Jiakun; Lu, Jian
Abstract: The $L_p$ dual Minkowski problem with $p<0<q$ is investigated in this paper. By proving a new existence result of solutions and constructing an example, we obtain the nonuniqueness of solutions to this problem.